Study of the smpact 14,5 mm kinetic action ammunition on the armored obstacle with additional armor - Dachkovskiy, Volodymyr; Kurtseitov, Tymur; Hudyma, Viktor; Yerhidzei, Kseniia; Novikova, Iryna (Social Development and Security, 2022)
Purpose: to consider the main approaches to assessing the level of stability of the armor barrier and to build a mathematical model of the effect of the kinetic energy of a 14.5 mm bullet on the hull of an armored combat vehicle with an additional armor barrier based on experimental data. Design/Method/Approach: to implement the purpose of the study, a laboratory experimental test of the main armor of the hull of armored combat vehicles with additional armor installed was carried out in order to obtain statistical data in accordance with the selected experimental research plan. Findings: the article on the basis of statistical data obtained during the experimental study developed a mathematical model of the impact of 14.5 mm weapons on the hull of armored combat vehicles with additional armor, which makes it possible to determine the optimal thickness of additional armor and the distance of additional armor to the main armor depending on the angle of inclination of the hull elements of armored combat vehicles. Theoretical implications: to assess the relative properties of the hull of armored combat vehicles with additional armor to the damaging energy of the destructive means used experimental-statistical method of mathematical modeling of the process of influence of the energy of the destructive means, in which the experiment is considered as the main source of information about the process, and the methods of probability theory and mathematical statistics - the main means of processing the results of the experiment. Practical implications: the developed mathematical model of the impact of 14.5 mm munitions on the hull of armored combat vehicles with additional armor makes it possible to assess the level of protection of armored combat vehicles at the stage of their modernization or design. Originality/Value: the value of the study is to determine the optimal parameters of additional armor to increase the level of protection of armored combat vehicles. Research limitations/Future research: the limitation of the study is that the mathematical model takes into account the angle of the meeting of the means of destruction with the hull of armored combat vehicles with installed additional armor, the distance from the additional armor to the hull, the thickness of the additional armor. Papertype: practical.